Age and sex influences on running mechanics and coordination variability - Boyer, K. A.; Freedman Silvernail, J.; Hamill, J. (Journal of Sports Sciences, 2017)
The purpose of this study was to examine the impact of age on running mechanics separately for male and female runners and to quantify sex differences in running mechanics and coordination variability for older runners. Kinematics and kinetics were captured for 20 younger (10 male) and 20 older (10 male) adults running overground at 3.5 m · s-1. A modified vector coding technique was used to calculate segment coordination variability. Lower extremity joint angles, moments and segment coordination variability were compared between age and sex groups. Significant sex-age interaction effects were found for heel-strike hip flexion and ankle in/eversion angles and peak ankle dorsiflexion angle. In older adults, mid-stance knee flexion angle, ankle inversion and abduction moments and hip abduction and external rotation moments differed by sex. Older compared with younger females had reduced coordination variability in the thigh-shank transverse plane couple but greater coordination variability for the shank rotation-foot eversion couple in early stance. These results suggest there may be a non-equivalent aging process in the movement mechanics for males and females. The age and sex differences in running mechanics and coordination variability highlight the need for sex-based analyses for future studies examining injury risk with age